Forage Characteristics of Bahiagrass Pastures Overseeded with 'Ubon' Stylosanthes. Issue 1 (28th May 2013) - Vendramini, J. M. B.; Silveira, M. L.; Aguiar, A. D.; Galzerano, L.; Valente, A. L.; Salvo, P.
Abstract : Overseeding warm‐season legumes into warm‐season perennial grass pastures is an option to improve forage quality and reduce the use of commercial N fertilizer. The objective of this study was to evaluate the effects of 'Ubon' stylo ( Stylosanthes guianensis var. vulgaris × var. pauciflora ) overseeded into bahiagrass ( Paspalum notatum Flügge) pastures on forage production and nutritive value. Treatments were overseeding stylo into bahiagrass pastures, bahiagrass pastures fertilized with 60 kg N/ha/year, or control (bahiagrass pasture with no N fertilization or legume) arranged in a randomized incomplete block design with three replicates. All treatments were continuously stocked using a fixed stocking rate with two heifers ( Bos spp.) per experimental unit. Forage evaluations were conducted every 28 days from July to October 2010 and 2011. Pastures fertilized with N had greater herbage mass (HM) and herbage allowance (HA) than overseeded or control treatments and there was no difference between overseeded and control treatments. Overseeded and N fertilized treatments had greater CP concentration than control. The proportion of Ubon stylo was constant in the overseeded pastures during the experiment (≈ 17%). The increased HM on N fertilized treatments may potentially allow greater stocking rates when compared to pastures overseeded with stylo.